Nephroprotective effect of Aloe barbadensis Miller against gentamicin induced nephrotoxicity in long evans male rats - Rahman, Farjana; Begum, Mahmuda; Chowdhury, Rama (Journal of Bangladesh Society of Physiologist, 2021)
Background: Kidney is an essential excretory organ of our body. It can be damaged by poisonous effect of chemicals, toxin, prolonged and uncontrolled use of drugs. Aloe vera is a herbal plant, it can be used for the prevention and treatment of kidney damage due to its natural compatability. Objective: To observe the nephroprotective effect of Aloe vera against gentamicin induced nephrotoxicity in long evans male rats. Method: This experimental study was conducted in the Department of Physiology, Sir Salimullah Medical College (SSMC), Dhaka from 1st January 2018 to 30th December 2018. For this, forty five (45) apparently healthy long evans male rats, 90-120 days old, weighing between 150-200 g were taken and divided into control group (group A) and experimental group (group B - Aloe vera pretreated and gentamicin treated group). Control group was subdivided into group A1 (baseline control group) and group A2 (gentamicin treated control group). Each group consisted of fifteen (15) rats. At the beginning of the study period initial body weight of rats were measured at day 01. All the rats received basal diet for thirty (30) days. Group A1 received only basal diet for 30 consecutive days (started from day 1 to day 30). In addition to basal diet, group A2 received injection gentamicin intraperitoneally once daily in the morning (80 mg/kg/day) for last 5 days (26th to 30th) of the study period. Again, in addition to basal diet, experimental group received Aloe vera orally (200 mg/kg/day) for 30 days and injection gentamicin intraperitoneally (80 mg/kg/day) for last 5 days (26th to 30th). After measuring final body weight all the rats were sacrificed on day 31. Blood sample was collected from heart. Serum levels of creatinine and urea were estimated for assessment of kidney function. Statistical analysis was done by one way ANOVA test followed by post hoc-Bonferroni test. Result: Mean serum levels of creatinine and urea were significantly (p<0.001) higher in gentamicin treated control group in comparison to that of base line control group. Again these levels were significantly (p<0.001) lower in Aloe vera pretreated and gentamicin treated group than that of gentamicin treated control group. Conclusion: From this study, it is concluded that Aloe vera has nephroprotective effect against gentamicin induced nephrotoxicity. J Bngladesh Soc Physiol 2021;16(1): 33-38